A Computed Tomographic and Pathological Study of Equine Cheek Teeth Infundibulae Extracted From Asymptomatic Horses. Part 2: MicroCT, Gross, and Histological Findings - Horbal, Apryle; Smith, Sionagh; Dixon, Padraic M. (Frontiers in Veterinary Science, 2019)
Background: Equine maxillary cheek teeth infundibulae are frequently affected by developmental and acquired disorders, but the imaging, gross, and histological features of normal and abnormal infundibulae remain incompletely understood. Objective: To perform MicroCT, gross examination, and histology on sectioned teeth and compare the imaging and anatomical findings. Study design:Ex vivo original study. Methods: Eight maxillary cheek teeth of different ages and with varying grades of unilateral (n = 5) or bilateral (n = 3) occlusal infundibular caries were extracted from equine heads obtained from an abattoir. The teeth were imaged by MicroCT, then transversely sectioned and grossly and histologically examined, with the imaging and gross and histological anatomical findings examined and compared. Results: Fifteen infundibulae, including two without occlusal caries had subocclusal cemental hypoplasia or caries. One infundibulum without occlusal caries had no subocclusal cemental defects. Histologically, hypoplastic cemental areas consisted of irregularly-shaped, wide central channels, with multiple, large, cylindrical side-branches that extended peripherally to a variable extent. Cementum with extensive, wide, empty channels, and cementum with a more irregular moth-eaten appearance had dark or eroded gross appearance and a low HU on CT. Some infundibulae had cement-free areas that only contained fragments of collagen-like material, especially at their apical aspects (apical cemental hypoplasia). Carious subocclusal areas had connections with the occlusal surface and had disrupted cemental architecture, including of their central vascular channel that, along with their side branches, contained degraded food, and cemental debris. Main Limitations: No clinical histories or accurate ages were available for these eight teeth. Conclusions: Hypoplastic cemental lesions, including at central linear and apical sites, histologically contain areas with multiple wide-branched, cylindrical channels or even areas of total cement hypoplasia visible on gross sections When such cemental defects contact the occlusal surface due to normal wear, food impaction, and caries can ensue.